2021
DOI: 10.3390/diagnostics11071297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating of Red Blood Cell Distribution Width, Comorbidities and Electrocardiographic Ratios as Predictors of Prognosis in Patients with Pulmonary Hypertension

Abstract: Pulmonary hypertension is a rare condition that impairs patients’ quality of life and life expectancy. The development of noninvasive instruments may help elucidate the prognosis of this cardiorespiratory disease. We aimed to evaluate the utility of routinely performed noninvasive test results as prognostic markers in patients with pulmonary hypertension. We enrolled 198 patients with mean pulmonary artery pressure >25 mmHg measured at cardiac catheterisation or echocardiographic pulmonary artery systolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Even within the normal reference range, a high RDW was substantially related to an elevated risk of all diseases (17). Many disorders, including heart failure (HF) and pulmonary hypertension (PH), have been associated with a substantial link between an increase in RDW and unfavorable outcomes (8,18). Recent research has shown a correlation between RDW and PE's prediction, severity, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even within the normal reference range, a high RDW was substantially related to an elevated risk of all diseases (17). Many disorders, including heart failure (HF) and pulmonary hypertension (PH), have been associated with a substantial link between an increase in RDW and unfavorable outcomes (8,18). Recent research has shown a correlation between RDW and PE's prediction, severity, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is also inexpensive, readily available, dependable, and widely used (6). It has been explored as a possible independent predictor of morbidity and mortality in several illnesses and disorders, including heart failure (HF), pulmonary hypertension, and myocardial infarction, as well as for patients in intensive care units (6)(7)(8). RDW levels may be a reliable and independent predictor of a higher death risk among individuals with PE (9).…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies have shown that RDW independently and directly predicts mortality in cardiovascular and other acute and chronic diseases, such as acute myocardial infarction, heart failure, pulmonary hypertension, ischemic stroke, coronavirus disease 2019, acute pancreatitis, and acute kidney injury. [5][6][7][8][9][10][11] A comprehensive meta-analysis of 31 studies and 3,487,896 patients found that elevated RDW was a risk factor for AIS. [12] A survey of 25,992 participants found that a 1% increment in RDW yielded a 13% higher risk of AIS.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
“…Open access kidney injury. [6][7][8][9][10][11][12] There is sufficient evidence to indicate that RDW is an effective parameter for predicting clinical prognosis and may have profound implications in clinical treatment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…RDW is a quantitative parameter that indicates the degree of volume variation in erythroid cells and is customarily used in haematology to help diagnose anaemia 5. Population-based studies have shown that RDW independently and directly predicts mortality in cardiovascular and other acute and chronic diseases such as AMI, heart failure, pulmonary hypertension, ischaemic stroke, coronavirus disease 2019, acute pancreatitis and acute kidney injury 6–12. There is sufficient evidence to indicate that RDW is an effective parameter for predicting clinical prognosis and may have profound implications in clinical treatment.…”
Section: Introductionmentioning
confidence: 99%